The Influence Of Online Sales Through Social Media and Mobile Applications Of Interest in Buying Customer Case Study ABC Store Palembang - Rika Kharlina Ekawati (Annual Research Seminar (ARS), 2016)
The development of internet and mobile in indonesia greatly increased in recent years .This means that marketers e-commerce relies heavily on the net in sell their products .The use of social media and applications mobile done to will attract customers to shop .In this research test influence online sales through social media and mobile application of interest in buying customers .The result showed that empirically is the sales through between online social media and mobile application of interest in buying customers .But in partial , the application mobile show an influence negatively on interest in buying customers .This is because pelangganyang still use website or social media first to see products and will install application mobile if they are interested to buy.